Extensive Neck Haematoma as an Extremely Rare Presentation of Thyroid Carcinoma: A Case Report - Hui, Lo Ren; Ibrahim, Fairuz Mohd; Abdullah, Khairudin; Ahmad, Nasriah; Hassan, Fazilah; Mohamad, Irfan (International Journal of Human and Health Sciences (IJHHS), 2020)
Anaplastic thyroid carcinoma (ATC) is uncommon but deadly. It is typically presented with fast growing neck mass, hoarseness or dysphagia. We report an extremely rare presentation of ATC in an elderly lady, with expanding ecchymosis involving laryngopharynx, neck and upper chest region, which causing upper airway obstruction. The rarity of presentation and the management dilemma were discussed. International Journal of Human and Health Sciences Vol. 04 No. 03 July’20 Page : 226-228